The mediation of customer satisfaction in the relationship between customer perceived value and loyalty in the banking sector of Pakistan using 2-stage structure equation modelling approach - Khan, Muhammad Imran; Jan, Muhammad Tahir; Aman, Qaiser; Faqir., Muhammad Shahid; Ali, Rafaqet (Asesoria & Tutorias Investigacion Cientifica Educacion, 2019)
The aim of the paper is to investigate the role of customer satisfaction as a mediator among perceived value and loyalty in four leading banks of Punjab, Pakistan. The study in nature is descriptive quantitative. The collected data went through exhaustive process of analyses, where reliability tests were conducts followed by factor analysis and finally a two-stage structural equation modelling. The results reveal reasonably high reliability, six-factor structure during exploratory factor analysis, and acceptable fit during confirmatory factor analysis and full-fledge structural modelling.